The mediating effect of social network identity management on the relationship between personality traits and social media addiction among pre-service teachers - Onur Isbulan; Emre Cam; Mark D. Griffiths (BMC Psychology, 2024)
Abstract Background The use of social media has become an important part individuals’ daily lives and is used in many daily life activities, such as social interaction, education, and shopping. However, with the increase in the use of social media, a minority of individuals can experience problematic use (and in extreme cases, ‘social media addiction’). The purpose of the present study was to examine the effect of personality traits on social media addiction and the mediating role of social network identity management in this relationship among preservice teachers. Methods The data were collected from 275 pre-service teachers at a university in Türkiye. The survey included the Big Five Inventory-10 (BFI-10), the Social Network Identity Management Scale, the Bergen Social Media Addiction Scale, and a personal information form. Results The findings of the study indicated that there was a relationship between personality traits, social network identity management, and social media addiction. Specifically, neuroticism was positively associated with social media addiction, whereas extraversion, agreeableness and conscientiousness were negatively associated. The results also indicated that social network identity management mediated the effect of personality traits on social media addiction. Conclusion Given that the present investigation was only a preliminary study, further research is needed to examine whether social network identity management is an important determinant in understanding the relationship between personality traits and social media addiction.